2015
DOI: 10.1111/cei.12592
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of host genetic variations in the genes of cytokines in critically ill patients

Abstract: SummaryHost genetic variations may influence a changing profile of biochemical markers and outcome in patients with trauma/injury. The objective of this study was to assess clinical associations of single nucleotide polymorphisms (SNPs) in the genes of cytokines in critically ill patients. A total of 430 patients were genotyped for SNPs in the genes of pro-(IL1B, IL6, IL8) and anti-inflammatory (IL4, IL10, IL13) cytokines. The main end-points were sepsis, mortality and adult respiratory distress syndrome (ARDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 96 publications
0
10
0
1
Order By: Relevance
“…The levels of LDH and CK signi cantly increased in patients with ARDS. LDH and CK were not only markers of in ammation but also indicators of prognosis in critical illness (22,23). Liu(24) et al reported that the patients with acute lung injury also had elevated levels of enzymes including LDH and CK due to in ammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of LDH and CK signi cantly increased in patients with ARDS. LDH and CK were not only markers of in ammation but also indicators of prognosis in critical illness (22,23). Liu(24) et al reported that the patients with acute lung injury also had elevated levels of enzymes including LDH and CK due to in ammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the next step, RNAse III endonuclease, also called Drosha, activates the pri-microRNAs. This reaction is catalyzed by the DiGeorge Syndrome Critical Region 8 (DGCR8) complex, which leads to the formation of pre-microRNAs [15,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74].…”
Section: Biochemical and Biosynthesis Aspects Of Micrornasmentioning
confidence: 99%
“…Results until now have shown association of the allele with higher plasma IL-8 levels, as well as with survival [194]. The A allele has been suggested to be associated with protection against sepsis [195], and also with increased risk of sepsis [196]. The heterozygote AT genotype has been associated with increased risk of developing severe sepsis [197].…”
Section: Il-8mentioning
confidence: 99%
“…Toll-like receptors (TLRs) -D299G allele of TLR4 gene associated with increased susceptibility to severe bacterial infections and Gram-negative sepsis [192,193] IL-8 -The 251A/T allele has been associated with survival [194], protection against sepsis [195], and also increased risk of sepsis [196] -The heterozygote AT genotype has been associated with increased risk of developing sepsis [197] -Male T allele carriers are more susceptible to sepsis [198] TNF-α -G-to-A polymorphism associated with sepsis [201] -G-to-A polymorphism associated with adverse outcomes in patients with severe sepsis and septic shock [199,200] -No association of G-to-A polymorphism and development of sepsis [202,203] -G-to-A polymorphism not associated with sepsis mortality [201] IL-6 -174 G/C polymorphism showed modest association with neonatal sepsis [209] -174 G/C polymorphism was associated with improved survival rates in patients with sepsis [207] -174 G/C polymorphism was not associated with a difference in survival [208] Angiotensin-converting enzyme (ACE)…”
Section: Diagnostic Significance Prognostic Significancementioning
confidence: 99%